2022
DOI: 10.3390/cancers14246170
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Age and Viral Status in EBV-Related Nasopharyngeal and HPV-Related Oropharyngeal Carcinoma Patients

Abstract: Background. The aim of this work was to analyze the interplay between age and viral status on the outcomes in loco-regionally advanced oropharyngeal and nasopharyngeal cancer patients treated with radiotherapy and different chemotherapy combinations. Methods. A retrospective (2006–2017) analysis was performed on non-metastatic loco-regionally advanced oropharyngeal (both HPV+ and HPV−) and EBV+ nasopharyngeal cancer patients (young: <65 years vs. elderly: ≥65 years) treated with radiotherapy with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…On the other hand, when adjusting for confounding factors such as disease stage, smoking, comorbidities and treatment intensity, no significant differences in terms of survival were observed. Hence, age has to be considered in the setting of the specific host and tumor-related features rather than independently [ 37 ]. Moreover, elderly patients tend to respond differently to the treatment; Wang et al showed that the addition of induction chemotherapy had no impact on survival compared to chemoradiotherapy alone and led to worse grade III to IV toxicities [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when adjusting for confounding factors such as disease stage, smoking, comorbidities and treatment intensity, no significant differences in terms of survival were observed. Hence, age has to be considered in the setting of the specific host and tumor-related features rather than independently [ 37 ]. Moreover, elderly patients tend to respond differently to the treatment; Wang et al showed that the addition of induction chemotherapy had no impact on survival compared to chemoradiotherapy alone and led to worse grade III to IV toxicities [ 38 ].…”
Section: Discussionmentioning
confidence: 99%